Design : intelligence made visible - Bayley, Stephen; Conran, Terence (Buffalo, N.Y. ; Richmond Hill, Ont. : Firefly Books, 2007)
Includes the leading names, movements, materials and processes such as furniture, fashion, cars, graphics, products, signs and symbols that have influenced the world of design.
A note on good design / Terence Conran -- A note on disegno / Stephen Bayley -- 1. An industrious love of art : the beginnings of design -- 2. Lawful prey : mass-consumption -- 3. A kilogram of stone or a kilogram of gold? : survival and revival of craft values -- 4. Hygiene of the optical : the romance of the machine -- 5. The cash value of art : America -- 6. La Ricostruzione : Italy since the Fifties -- 7. Ugly, inefficient, depressing chaos : symbolism and consumer psychology -- 8. All that is solid melts into air : design since the Eighties -- A-Z entries -- National characteristics -- Museums & institutions -- Index -- Acknowledgements.
Cover title.
Includes bibliographical references and index.
Keywords: Industrial design; Art and design; Design -- History; Fashion design